Study of Lau fringes generated by a photorefractive volume grating - Forte, Gustavo Fabian (2017)
In this work the Lau fringes generated by using a combination of an amplitude grating and a photorefractive volume phase grating is theoretically and experimentally analyzed. A model based on the path integral formalism to calculate the patterns intensity is employed. We show that the Lau pattern behavior is governed by the output pupil diameter of the imaging recording system, the DC external electric field and the crystal thickness. The introduction of a phase modulation that gathers the previously mentioned parameters allows determining the condition to optimize the fringe visibility. In this case, the visibility maintains a sinusoidal dependence as it happened with planar grating experiments. The experimental results confirm the theoretical model proposed.